Evaluation of rock slope deterioration based on granite and schist rock slopes - Roslan R.; Omar R.C.; Taha H.; Baharuddin I.N.Z.; Ahmad F. (International Association of Lowland Technology, 2023)
Compressive strength; Deterioration; Durability; Granite; Infiltration; Load testing; Testing; Direct shear box test; Engineering characteristics; Field observations; Physical and mechanical properties; Schmidt hammer tests; Slope instability; Uniaxial compressive strength; Weathering grades; Weathering; compressive strength; granite; landslide; mechanical property; schist; slope failure; slope stability; uniaxial strength; Malaysia